The high energy X-ray probe (HEX-P): instrument and mission profile - Madsen, Kristin K.; García, Javier A.; Stern, Daniel; Amini, Rashied; Basso, Stefano; Coutinho, Diogo; Grefenstette, Brian W.; Kenyon, Steven; Moretti, Alberto; Morrissey, Patrick; Nandra, Kirpal; Pareschi, Giovanni; et al. (Frontiers in Astronomy and Space Sciences, 2024)
The High Energy X-ray Probe (HEX-P) is a proposed NASA probe-class mission that combines the power of high angular resolution with a broad X-ray bandpass to provide the necessary leap in capabilities to address the important astrophysical questions of the next decade. HEX-P achieves breakthrough performance by combining technologies developed by experienced international partners. To meet the science goals, the payload consists of a suite of co-aligned X-ray telescopes designed to cover the 0.2–80 keV bandpass. The High Energy Telescope (HET) has an effective bandpass of 2–80 keV, and the Low Energy Telescope (LET) has an effective bandpass of 0.2–20 keV. HEX-P will be launched into L1 to enable high observing efficiency, and the combination of bandpass and high observing efficiency delivers a powerful platform for broad science to serve a wide community. The baseline mission is 5 years, with 30% of the observing time dedicated to the PI-led program and 70% to a General Observer (GO) program. The General Observer program will be executed along with the PI-led program.